Determination of well flat band condition in thin film FDSOI transistors using C-V measurement for accurate parameter extraction. (January 2018) - Mohamad, B.; Leroux, C.; Reimbold, G.; Ghibaudo, G.
Highlights: A new method is proposed to extract the FDSOI well flat band voltage VFB, W . This experimental method enables an accurate and direct evaluation of WFeff . An accurate and simple extraction of the channel thickness is presented. The existence of a dipole at the SiGe/SiO2 interface is experimentally proved. Abstract: For advanced gate stacks, effective work function (WFeff ) and equivalent oxide thickness (EOT) are fundamental parameters for technology optimization. On FDSOI transistors, and contrary to the bulk technologies, while EOT can still be extracted at strong inversion from the typical gate-to-channel capacitance (Cgc ), it is no longer the case for WFeff due to the disappearance of an observable flat band condition on capacitance characteristics. In this work, a new experimental method, the Cbg (VBG ) characteristic, is proposed in order to extract the well flat band condition (VFB, W ). This characteristic enables an accurate and direct evaluation of WFeff . Moreover, using the previous extraction of the gate oxide (tfox ), and buried oxide (tbox ) from typical capacitance characteristics (Cgc and Cbc ), it allows the extraction of the channel thickness (tch ). Furthermore, the measurement of the well flat band condition on Cbg (VBG ) characteristics for two different Si and SiGe channel also proves the existence of a dipole at the SiGe/SiO2 interface.